Testicular mitochondrial redox imbalance and impaired oxidative phosphorylation underlie microplastic-induced testicular dysfunction in Wistar rats - Kehinde, Samuel Abiodun; Fatokun, Tolulope Peter; Praveena, Sarva Mangala; Olajide, Abosede Temitope; Tham, Chau Ling; Pereira, Mariana Teles; Chusri, Sasitorn (Frontiers in Toxicology, 2026)
Polyethylene microplastics (PE-MPs), now pervasive environmental contaminants, have been implicated in reproductive toxicity, but their mechanistic effects on testicular function remain poorly defined. This study investigates the mechanistic basis of PE-MPs–induced male reproductive toxicity in a rodent model (Wistar rats), with a specific focus on testicular mitochondrial redox homeostasis and oxidative phosphorylation. By integrating mitochondrial bioenergetics, redox signaling, histopathology, and reproductive endpoints, the work advances mechanistic toxicology insights relevant to environmental reproductive health. Fifteen male rats were randomly divided into three groups: control, and PE-MPs treated groups receiving 15 or 60 mg/kg body weight orally for 28 days. Testicular mitochondria were isolated to evaluate activities of tricarboxylic acid (TCA) cycle enzymes, citrate synthase (CS), isocitrate dehydrogenase (IDH), succinate dehydrogenase (SDH), and malate dehydrogenase (MDH), as well as respiratory chain complexes I–IV. Mitochondrial redox balance indices, including malondialdehyde (MDA), myeloperoxidase (MPO), reduced glutathione (GSH), catalase (CAT), and superoxide dismutase (SOD), were also assessed. PE-MP exposure induced a dose-dependent suppression of TCA cycle and electron transport activities, with CS and SDH inhibited by up to 50% at the highest dose suggesting a broad inhibition of electron transport and ATP synthesis. These mitochondrial impairments coincided with elevated MDA and MPO levels, and significant depletion of GSH, CAT, and SOD, indicating profound mitochondrial oxidative distress. These mitochondrial disturbances correlated with histological evidence of testicular degeneration and decreased testosterone levels. Collectively, the findings of this study highlight that PE-MPs compromise testicular bioenergetics and function by disrupting testicular oxidative phosphorylation and redox homeostasis, leading to mitochondrial dysfunction, structural degeneration, and impaired steroidogenesis, providing mechanistic insight into microplastic-induced male infertility. Understanding this bioenergetic collapse provides a biochemical framework for assessing the reproductive toxicity of microplastics and underscores the urgency of mitigating their exposure in vulnerable populations.